2019
DOI: 10.1002/jsfa.10161
|View full text |Cite
|
Sign up to set email alerts
|

Root colonization by heavy metal resistant Enterobacter and its influence on metal induced oxidative stress on Cajanus cajan

Abstract: BACKGROUND: Heavy metal resistant bacterium Enterobacter sp. C1D was evaluated for cadmium (Cd) mediated exopolysaccharide production, biofilm formation and legume root colonization ability under Cd stress to alleviate metal induced stress. RESULTS:The plant was sensitive to Cd (IC 50 3-4 g mL −1 ), whereas the bacterium showed high Cd tolerance (MIC 99 120 g mL −1 ). Confocal laser scanning microscopy of the Cajanus cajan roots showed heavy loads of green fluorescence protein labelled Enterobacter sp. C1D on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This result also positively correlated with the results of Enterobacter sp. ( Abbas et al, 2014 ; Sharma et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result also positively correlated with the results of Enterobacter sp. ( Abbas et al, 2014 ; Sharma et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Increment of the shoot and root length in rice plants after application of Serratia marcescens ( Kotoky et al, 2019 ) was observed under Cd stress. Moreover, the biomass increasing property (under Cd stress) of AS10 indicates the bioremediation capability of the isolate ( Lin et al, 2016 ; Sharma et al, 2020 ). PGPR-mediated improvement in morphological growth indices under Cd stress has also been narrated earlier by other workers in this field ( Ahmad et al, 2016 ; Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…They are also involved in nitrogen fixation, phytohormones secretion, and acquisition of nutrients, thereby improving the growth of the plant. Root exudates are known to be produced by plants that act as the source of energy for endophytic microbes associated with them [72]. While endophytic organisms were colonizing the plants at an early stage, there is the production of exopolysaccharides (EPS) from bacterial cells that alleviate its attachment to the surface of the root and likewise prevent bacterial cells from oxidative damage [73].…”
Section: Differences In the Mechanisms Of Overcoming Stress By Plants...mentioning
confidence: 99%
“…A strong resistance to heavy metals was reported for Enterobacter spp. found in contaminated soil and sediments (Neeta et al, 2016;Chen et al, 2017;Sharma et al, 2020). Moreover, this Gram-negative enteric bacteria have already been successfully inoculated to alleviated HM stress in other crops: soybean (Kang et al, 2015), rice (Mitra et al, 2018), and hyperaccumulator plants (Whiting et al, 2001).…”
Section: Hemp and Giant Reed Phyto-assisted Bioremediation Potentialmentioning
confidence: 99%